Ontology of scientific and technical terminology and questions of its codification in lexicographic descriptions (Eurasian Journal of Philology Science and Education, 2018)
The article is devoted to the ontology of scientific-technical terminology and its codification inthe lexicographical words and aimed at defining key concepts terminology and codification as natureof the term. The key categories of modern terminology are established, the scientific definition ofthe word-term, terminology as a system is given. When determining the nature of the scientific andtechnical term, the place and its functional significance are determined in the general system of the vocabulary of any language. The article also explores the semantic structure of the scientific – technicalterm and reflects in it the latest achievements of science and technology of our days. No coincidencethat the number of new terms exceeds the number of neutral common vocabulary. The article alsogives description complex of the syntactic functions of the word-term, its properties compatibility. Allthis is within the competence of the lexicographical codification of the language. are considered Thescientific and technical terms of the electric power industry , which reflect the possibility of combiningwords in speech activity, and they are much broader than the combinations offered by dictionaries. Itis argued that an understanding of the linguistic compatibility of terms helps in the correct use of theconcept in speech